Improving accountability of village funds through village financial management based on government accounting standards - Rosnidah, Ida; Muna, Arinal; Musyaffi, Ayatulloh Michael; Fariani, Nelia (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2021)
The government organizes the village fund within the framework of fulfilling the ideals of the Indonesian people, namely the existence of equal distribution in each region. The amount of village funds requires the village government to make transparent financial reporting. However, not all village governments are able to manage village funds properly. So, this dedication is to help the village government make and request financial reports according to the standards. This activity is carried out within a period of 2 months with several meetings. Each participant will be guided to be able to manage finances so that they can be requested. The object of this research is the village head, village secretary, finance department, and treasurer in Battembat village, Tengah Tani sub-district, Cirebon. The results of this study it is known that the finance department has been able to make financial records both manually and in systems. Financial information in the financial process into financial reports is sufficient for decision-making material. According to information, this finance section has also been adapted to the Siskeudes application which is also supported by the program section.